2013
DOI: 10.1523/jneurosci.4654-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypical Alterations in Cortical Patterning Are Associated with Maternal Illness-Induced Placental Dysfunction

Abstract: We have previously shown in mice that cytokine-mediated damage to the placenta can temporarily limit the flow of nutrients and oxygen to the fetus. The placental vulnerability is pronounced before embryonic day 11, when even mild immune challenge results in fetal loss. As gestation progresses, the placenta becomes increasingly resilient to maternal inflammation, but there is a narrow window in gestation when the placenta is still vulnerable to immune challenge yet resistant enough to allow for fetal survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…Our results are in agreement with the findings from studies in mice that analysed the development of the neocortex under inflammatory conditions. Similar to the in vivo model, we also observed a reduced expression of the neocortex development regulators Tbr1, 36 Tbr2, 37 and Pax6 38 in response to inflammation and pro-inflammatory cytokines. The data thus show that our in vitro model of an endothelial barrier co-cultured with neural tissue spheroids is able to reflect crucial aspects of neuroinflammation during neocortex formation.…”
Section: -10supporting
confidence: 81%
“…Our results are in agreement with the findings from studies in mice that analysed the development of the neocortex under inflammatory conditions. Similar to the in vivo model, we also observed a reduced expression of the neocortex development regulators Tbr1, 36 Tbr2, 37 and Pax6 38 in response to inflammation and pro-inflammatory cytokines. The data thus show that our in vitro model of an endothelial barrier co-cultured with neural tissue spheroids is able to reflect crucial aspects of neuroinflammation during neocortex formation.…”
Section: -10supporting
confidence: 81%
“…This may further lead to white matter injury, with consequences for cerebral palsy and related demyelinating diseases in premature infants91037. Increased cortex volume or thickness is a consistent result supported by others2744, but reduced cortical volume26 or thickness30 is not consistently observed. These discrepancies may be due to differences in LPS dosage and the time and brain region of post-injection observation.…”
Section: Discussionmentioning
confidence: 71%
“…Specific genes such as Tbr1 (T-box brain 1), Ctip2 (COUP-TF interacting protein 2), and Satb2 (special AT-rich sequence binding protein 2) play important roles at each step during differentiation, and disruption leads to profound cortical malformation2045. Carpentier and colleagues have shown that there are stereotypical alterations in cortical patterning in LPS-exposed mice30, although this has not yet been replicated in other studies. Even less is known about how NAC influences LPS-affected neural laminar positioning.…”
Section: Resultsmentioning
confidence: 99%
“…Normal development of the fetal brain can be affected by several factors, including genetic background, inflammatory insults, as well as changes in extrinsic and intrinsic signals (Carpentier et al, 2013;Haydar et al, 1996). It emerges that oxygen signaling in neuroprogenitors appears to be a crucial mechanism for cell survival during brain development.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the embryonic forebrain is an extremely wellorchestrated process controlled by intrinsic and extrinsic signals delivered to the cells in a strict temporal sequence (Carpentier et al, 2013;Dehay and Kennedy, 2007;Nieto et al, 2004;Roy et al, 2004). Disruptions of these events alter cortical growth and design because they regulate the development of progenitor cell types.…”
Section: Introductionmentioning
confidence: 99%